Intervensi Untuk Meningkatan Status Nutrisi Pasien Hemodialisa : Systematic Review - Ferry Adref; Syahrul Syahrul; Ariyanti Saleh (Jurnal Keperawatan Muhammadiyah, 2019)
Hemodialysis is a therapy in patients with kidney failure associated with inflammatory processes and malnutrition. This systematic review aims to identify and assess the effectiveness of nursing interventions that have an impact on the nutritional status of patients with hemodialysis. A systematic search was carried out in several international data bases, namely: PuBMED, ProQUEST, and Science Direct. We included 9 studies related to intervention to improve the nutritional status of hemodialysis patients who have been tested for quality with CASP and JBI. There are 3 studies evaluating educational and information interventions, 3 studies evaluating enriched food supplementation, 2 studies evaluating dietary interventions, and 1 studi evaluating physical exercise interventions. The studi included significant results on positive changes in the nutritional status of hemodialysis patients, ie there was an increase in food intake, nutritional laboratory markers, anthropometrics and there was a decrease in serum trigleserid levels, IDGW lines and dry weight, and no PEM condition was found after the intervention was given in time certain. The choice of education and information interventions, the provision of enriched food supplements, diet and physical exercise can provide a good effect on improving the nutritional status of patients with hemodialysis, but resources and cost effectiveness need to be taken into consideration.